Experiences and perceptions in an ESL academic writing peer response group = Experiencias y percepciones del proceso de revisión entre pares en un seminario de inglés para fines - Rollinson, Paul (Estudios Ingleses de la Universidad Complutense, 2004)
The following article traces the experiences of four Spanish students and their perceptions of the peer response process, both as responders and writers, during a twelve week (36 hour) EAP writing workshop. In a homogeneous, motivated and collaborative group, what comes to light is the uniqueness of the individual writers in terms of their reactions to the feedback they receive, and to the peer response activity itself. Each writer displays a different profile in terms of her willingness to accept comments, the use she makes of different types of feedback, and her overall perception of the significance and value of different aspects of the peer response process. The implications are considerable: while recent L2 writing research broadly suggests that peer response groups can perform a useful complementary function in the writing classroom, this study concludes that if response groups are to work for every writer, then current notions of preliminary peer training must be extended and personalized to take into account the ongoing needs of the individual operating within the group.